2019
DOI: 10.30534/ijatcse/2019/07852019
|View full text |Cite
|
Sign up to set email alerts
|

A Naïve Bayes Sentiment Analysis for Fintech Mobile Application User Review in Indonesia

Abstract: The growth of Fintech industries in Indonesia, as the 5 th most internet users in the world, is tremendous, with a predicted of 16,3% year on year user growth and a total of $176,75 Million USD in investment on Fintech Startup it has become one of the biggest potential market in the world. Therefore, with this fast-growing market, Fintech Companies need to know their user opinion in Realtime in order to face their competitor on the market. Existing user review on Application Store already existed but there are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…All data in the text mining is in the form of an object ( ), while is a class label assigned to . Also, Classification techniques are processes that are implemented to label data, also known as a descriptive classifier for the new sample that belongs to the predictive model [35].…”
Section: Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…All data in the text mining is in the form of an object ( ), while is a class label assigned to . Also, Classification techniques are processes that are implemented to label data, also known as a descriptive classifier for the new sample that belongs to the predictive model [35].…”
Section: Classificationmentioning
confidence: 99%
“…Inconsistent, Inaccurate, incomplete, and contaminated data analysis can lead to having poor quality and shallow results. Incorrect text mining means having misleading results; this may occur due to data entry errors [35]. Nevertheless, the main target of preparation and pre-processing technique is to indicate the insufficiencies and limitations of text mining.…”
Section: Translation Datamentioning
confidence: 99%
“…Both datasets also implemented data cleansing. Results showed that a 3% margin of accuracy with Bahasa Indonesia and English compared with Bahasa Only [9].…”
Section: A Naïve Bayes Sentiment Analysis For Fintech Mobile Application User Review In Indonesiamentioning
confidence: 99%
“…Putra et al, [12], Oueslati el at., [13] conducted studies on utilizing hashtags and emoticons in tweets to build training datasets for sentiment analysis. The basic idea is to collect tweets containing the sentiment hashtags (e.g., "#sucks", "#notcute") or emoticons (e.g., ":)", ": D", ": -("), and label each tweet as positive or negative based on the polarity of hashtags and emoticons.…”
Section: Emotion Detection Using Hashtags and Emoticonsmentioning
confidence: 99%